Effect of Environmental Stressors, Xenobiotics, and Oxidative Stress on Male Reproductive and Sexual Health - Madhu, Nithar Ranjan; Sarkar, Bhanumati; Slama, Petr; Jha, Niraj Kumar; Ghorai, Sudipta Kumar; Jana, Sandip Kumar; Govindasamy, Kadirvel; Massanyi, Peter; Lukac, Norbert; Kumar, Dhruv; Kalita, Jogen C; Kesari, Kavindra Kumar; et al. (Advances in experimental medicine and biology, 2022)
This article examines the environmental factor-induced oxidative stress (OS) and their effects on male reproductive and sexual health. There are several factors that induce OS, i.e. radition, metal contamination, xenobiotic compounds, and cigarette smoke and lead to cause toxicity in the cells through metabolic or bioenergetic processes. These environmental factors may produce free radicals and enhance the reactive oxygen species (ROS). Free radicals are molecules that include oxygen and disbalance the amount of electrons that can create major chemical chains in the body and cause oxidation. Oxidative damage to cells may impair male fertility and lead to abnormal embryonic development. Moreover, it does not only cause a vast number of health issues such as ageing, cancer, atherosclerosis, insulin resistance, diabetes mellitus, cardiovascular diseases, ischemia-reperfusion injury, and neurodegenerative disorders but also decreases the motility of spermatozoa while increasing sperm DNA damage, impairing sperm mitochondrial membrane lipids and protein kinases. This chapter mainly focuses on the environmental stressors with further discussion on the mechanisms causing congenital impairments due to poor sexual health and transmitting altered signal transduction pathways in male gonadal tissues.
Keywords: Sexual Health; Oxidative Stress; oxidační stres; sexuální zdraví; Seeds; volné radikály; Free Radicals; semena rostlinná